Mobile technology to promote education 4.0 in Vietnam - Loc My Thi Nguyen; Tuong Sy Hoang (Vietnam Journal of Education, 2020)
Currently, with development of technology, the use of gadgets like smart devices (smartphones, tablets) is becoming more common. In recent years, mobile technologies play an increasingly important role in students’ lives, study and scientific research. In addition, currently most students in higher education institutions use smartphones. Many universities use electronic devices such as smart phones, laptops, computers, and tablets as teaching devices and building websites that run on mobile platforms or developing applications that can be easily downloaded from google play or Apple store. Therefore, this article focuses on analyzing the perspectives as well as the application of learning on mobile devices in higher education 4.0. Surveys of students owning a mobile device and doing their learning on a mobile phone show that the currently students owning mobile devices is high and will continue to increase. The data was analyzed through the calculation of the proportion of responses in the questionnaires. The article also summarizes the results of short discussions about the results of the research, finding that mobile technologies play an important role in teaching and learning in the current context of higher education in Vietnam. Based on the results, the authors recommend that more studies should be done to provide knowledge regarding the application and development of mobile technologies in learning and research of students towards the era of industrial revolution 4.0 (IR4).